Variation of pH and of nutrients content of rainfall and throughfall in a southern Bahia cacao agrosystem - Rodrigues, Antonio Carlos da Gama; de Miranda, Ricardo Augusto Calheiros (Pesquisa Agropecuaria Brasileira, 1992)
The acidity of the rainfall and its effect on the li-beration of nutrients were studied in a Catongo cocoa plot grown in Typic Tropudalf soil and shaded by Erythrina fusca Lour. The rainfall pH, 7.11 in average, indicated that the acidity is not a responsible factor in the liberation of nutrients. The throughfall acidity showed a slight decrease and had mean value of pH 6.89. The increases of Ca, Mg, K and Na in the through-fall were 298%, 492%, 530% and 24% respectively.